Sakhalin island and the one of its researcher - Zimina Tatiana Alekseevna - E.G. Dobrutskaya (Ovoŝi Rossii, 2012)
Sakhalin island is one of the regions of Russia with extreme climatic conditions. The first scientist in the field of biology, agriculture, and agro-ecology of Sakhalin region was Zimina Tatiana Alekseevna, Doctor of agricultural science. On the 26th November of 2011 the scientific community of genetics and plant breeders celebrated the 90-th birthday of Zimina T.A. The stuff of VNIISSOK cherish the memory of her as one of the talented scientist and devotee citizen.